(untitled) (Czech Journal of International Relations, 2000)
Max-Stephan Schulze (ed.): Western Europe - Economic and Social Change since 1945. 1st ed. Longman: London and New York, 1999, 408 stran, ISBN 0-582-29199-2 PPR.